STUDI PERENCANAAN POLA OPERASI EMBUNG BENGAWAN UNTUK KEBUTUHAN AIR BAKU KOTA TARAKAN - Rosmalia Handayani; Risdayana Risdayana (Civil Engineering Scientific Journal, 2026)
ABSTRACT: The construction of the Bengawan Reservoir is a problem regarding the need for raw water in Tarakan City. Because of this problem, it is necessary to carry out a potential study to plan the operation pattern of the Bengawan Reservoir to meet the raw water needs of the Bengawan Reservoir so that it can resolve some of the raw water problems in Tarakan City. The methods used in this research are the F.J Mock method which is used to calculate water availability, the Modified Penman method to calculate potential evapotranspiration and the Wiebull equation to determine the probability of discharge reliability. From the simulation results of the operation pattern of the Bengawan Embung reservoir, it was found that the reliability of the reservoir reservoir in meeting raw water needs. for the West Tarakan Region with each condition the water discharge is sufficient to have 100% reliability to serve 88,937 people, normal water discharge with 100% reliability to serve 88,937 people, low water discharge with 75% reliability to serve 66,703 people, reliable water discharge with reliability 70% capable of serving 62,256 people and dry water discharge with 59% reliability capable of serving 52,473 people. For the North Tarakan Region, with each condition the water flow is sufficient to have 100% reliability to serve 43,471 people, normal water flow with 100% reliability to serve 43,471 people, low water flow with 99% reliability to serve 43,036 people, reliable water flow with reliability 100% to serve 43,471 people and dry water discharge with 90% reliability able to serve 39,124 people. Keywords : inflow, outflow, operating patterns, embung operation simulation ABSTRAK: Pembangunan Embung Bengawan adalah adanya permasalahan akan kebutuhan air baku di Kota Tarakan, karena adanya permasalahan tersebut, maka perlu dilakukan potensi suatu studi untuk merencanakan pola operasi Embung Bengawan untuk memenuhi kebutuhan air baku pada Embung Bengawan sehingga dapat meyelesaikan sebagian permasalahan air baku di Kota Tarakan. Adapun metode yang digunakan dalam Penelitian ini yaitu metode F.J Mock yang digunakan untuk menghitung ketersediaan air, metode Penman Modifikasi untuk menghitung evapotranspirasi potensial dan persamaan Wiebull untuk menentukan probabilitas keandalan debit. Dari hasil simulasi pola operasi tampungan Embung bengawan didapatkan keandalan tampungan embung dalam memenuhi kebutuhan air baku. untuk Wilayah Tarakan Barat dengan masing-masing kondisi debit air cukup memiliki keandalan 100% untuk melayani 88.937 jiwa, debit air normal dengan keandalan 100% untuk melayani 88.937 jiwa, debit air rendah dengan keandalan 75% mampu melayani 66.703 jiwa, debit air andalan dengan keandalan 70% mampu melayani 62.256 jiwa dan debit air kering dengan keandalan 59% mampu melayani 52.473 jiwa. Untuk Wilayah Tarakan Utara dengan masing-masing kondisi debit air cukup memiliki keandalan 100% untuk melayani 43.471 jiwa, debit air normal dengan keandalan 100% untuk melayani 43.471 jiwa, debit air rendah dengan keandalan 99% untuk melayani 43.036 jiwa, debit air andalan dengan keandalan 100% untuk melayani 43.471 jiwa dan debit air kering dengan keandalan 90% mampu melayani 39.124 jiwa.Kata kunci : inflow, outflow, pola operasi, simulasi operasi embung